IMPACT ON CONSUMER PERCEPTION TOWARDS GREEN MARKETING IN FAST MOVING CONSUMER GOODS WITH SPECIAL REFERENCE TO CHENNAI - Dr.J.Yamuna (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Environmentally friendly products are request- acquainted products that beget minimum environmental declination and their product is linked to a product development process that's structured in a way that considers the impacts that can be caused to the terrain throughout their cycle. Fast – moving consumer goods are products that vend snappily at fairly low cost. These goods are bought constantly, are consumed fleetly, are priced low, and are vended in large amounts. They also have a high development when they’re on the shelf at the store. Thus, the study named “Impact on consumer perception towards green marketing in presto moving consumer goods with special reference to Chennai”. The study using a questionnaire and the total sample composed of 120 replies among the Chennai. A questionnaire is designed to find out the request mindfulness of Eco-friendly products, to assay the perception of consumers and also to identify the consumer’s amenability to pay for Eco-friendly products. The data is also been collected from colourful secondary sources. The results illustrate that maturity of the consumers aren't apprehensive of Eco – friendly FMCG products available in the request. Indeed, if the price is slightly high comparing to the conventional products.